Creating winning bids - Sawczuk, Basil (London : RIBA Publishing, 2013)
'Creating Winning Bids' sets out the key stages in the production of a winning bid. Based on tried and tested methods, and using a simple step-by-step process, it will improve your chances of success in what can otherwise seem a daunting and complex process.
Includes index.
Keywords: Letting of contracts; Proposal writing in business; Proposal writing in public contracting; Construction contracts; Architectural contracts